Metrics for software conceptual models - Genero, Marcela, 1966-; Piattini, Mario, 1966-; Calero, Coral, 1968- (London : Imperial College Press, 2005)
The idea that "measuring quality is the key to developing high-qualitysoftware systems" is gaining relevance. Moreover, it is widelyrecognised that the key to obtaining better software systems is tomeasure the quality characteristics of early artefacts, produced atthe conceptual modelling phase
Preface; Chapter 1 Towards a Framework for Conceptual Modelling Quality Mario Piattini, Marcela Genero, Geert Poels and Jim Nelson; Chapter 2 A Proposal of a Measure of Completeness for Conceptual Models Oscar Dieste, Marcela Genero, Natalia Juristo and Ana M. Moreno; Chapter 3 Metrics for Use Cases: A Survey of Current Proposals Beatriz Bernardez, Amador Duran and Marcela Genero; Chapter 4 Defining and Validating Metrics for UML Class Diagrams Marcela Genero, Geert Poels, Esperanza Manso and Mario Piattini.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Computer software -- Mathematical models; Logiciels -- Modèles mathématiques.; REFERENCE -- General; Computer software -- Mathematical models; Computer software -- Mathematical models